Revisión de las metodologías empleadas en la estimación y cuantificación de material particulado resuspendido (2022)
The objective of this work is to make a compilation of those methodologies used in the estimation and quantification of resuspended particulate matter that is influenced by vehicular activity on paved and unpaved roads. Through the revision of the protocol established by the Environmental Protection Agency in the AP-42, several articles are presented in which this methodology is implemented in large cities such as Barcelona, ​​Berlin, Zurich, among others, where pollution by particulate matter is high. With variations ranging from adjustments in mathematical models to the use of more sophisticated measurement instruments that allow the quantification of specifically resuspended particulate matter, it is found that there is a limitation when implementing the EPA methodology since what is done Throughout the entire process, it is an overestimation of the resuspended particulate matter and a more real value is not reached.